Treatment of iron ore using biomass waste for ironmaking - Mohamad Selamat, Norfazilah; Purwanto, Hadi; Fairos, Siti (2011)
Mini blast furnace ironmaking projects have been constructed to meet the demand of domestic steel in Malaysia. However, Malaysia only has low grade iron ore instead of commercially high grade ore as raw material. The use of low grade ore will cause in extra energy consumption to release combined water in the ore. Palm oil industry releases a lot of biomass waste such as kernel shell that is mostly not utilized effectively as energy source in Malaysia. Process has been proposed to utilize the kernel shell to treat domestic low grade iron ore for iron making. In this experiment, the ore was treated with kernel shell at desired temperature in electric tube furnace resulted pre-reduced ore. Ash added as carbon during grinding process will help reduction process. This material can be pellet for raw materials in blast furnace. Conversion of low grade iron ore to hematite and magnetite was caused by reduction process by reducing gases produced form gasification of kernel shell during at high heating. Thus, the low grade iron ore treated by biomass will replace some part of coal in iron making by doping carbon at the ore and yet reduced of CO2 emission instead of using fossil fuel.